2019
DOI: 10.1021/acssuschemeng.8b05908
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanoparticle-Stabilized Pickering Emulsion as a Sustainable and High-Performance Interfacial Catalysis Platform for Enzymatic Esterification/Transesterification

Abstract: A sustainable and efficient reaction system for enzymatic oil modification is imperative for the food industry. Given the interfacial activation effect of lipase, the sufficient oil–water interface is vital for excellent catalytic activity of lipase. In the present study, a Pickering emulsion reaction system was prepared through directly using reactants as the oil phase and stabilized by mesoporous carbon spheres (MCS) after immobilization of lipase AYS (Candida rugosa, lipase@MCS). Lipase@MCS worked as both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 53 publications
1
69
0
Order By: Relevance
“…This stimuli responsiveness allowed the controllable emulsification and demulsification, which were successfully explored for oil recovery [20] and chemocatalysis [21] . However, until now, stimuli‐responsive emulsions for biocatalysis have been relatively underdeveloped, [13c, 22] and to the best of our knowledge, they have never been explored for multienzyme cascades despite their potential to improve reaction compatibility and reduce cross‐reactivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stimuli responsiveness allowed the controllable emulsification and demulsification, which were successfully explored for oil recovery [20] and chemocatalysis [21] . However, until now, stimuli‐responsive emulsions for biocatalysis have been relatively underdeveloped, [13c, 22] and to the best of our knowledge, they have never been explored for multienzyme cascades despite their potential to improve reaction compatibility and reduce cross‐reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…These benefits, especially their large interface, have promoted rapidly the field of "emulsion biocatalysis" to address a wide range of synthetic challenges to date. [10] For instance, microemulsions, [11] miniemulsions, [12] and Pickering emulsions [13] were employed to encapsulate enzymes for the single-step enantioselective reduction, hydrolysis, and esterification. Recently, we further advanced the field by developing multi-compartmentalized emulsion biocatalysis for benzoin condensation and carbonyl reduction.…”
mentioning
confidence: 99%
“…1 In recent years, the enzyme-catalyzed synthesis of phytosterol esters has attracted increasing attention as these methods have advantages of having mild and environmentally friendly reaction conditions and fewer side products. 1,[14][15][16][17][18][19][20] However, its high cost and low reliability have great limit its large-scale industrial applications. 1 Previous studies have indicated that the solubility of phytosterol unsaturated fatty acid esters in edible oils (e.g., soybean oil) was up to 10 times than phytosterol saturated fatty acid esters.…”
Section: Introductionmentioning
confidence: 99%
“…10 Particle-stabilized emulsion, also known as Pickering emulsion, has received considerable interest in biphasic enzymatic catalysis. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The novel platform combines the advantages of enhanced stability, improved biocompatibility, and ease of product/catalyst separation. 13,14 Given that the involved reactants are organic-soluble, water-in-oil (w/o) Pickering emulsions with oil as the continuous phase are more preferable for feasible extraction of products and reuse of catalysts.…”
Section: Introductionmentioning
confidence: 99%